Neutrophil–lymphocyte ratio: a novel predictor for short‐term prognosis in acute‐on‐chronic hepatitis B liver failure. Issue 7 (28th August 2013) - Liu, H.; Zhang, H.; Wan, G.; Sang, Y.; Chang, Y.; Wang, X.; Zeng, H.
Summary Acute‐on‐chronic hepatitis B liver failure (ACHBLF) has a poor prognosis in patients with hepatitis B virus infection. The role of the neutrophil–lymphocyte ratio (NLR), which reflects the inflammatory status of the patient before treatment, has never been studied in this setting. To investigate the predictive value of NLR in patients with ACHBLF, a retrospective cohort with 216 patients and a prospective validation cohort with 73 patients were recruited. Multivariate analyses showed that total bilirubin (TBIL), NLR, age and model for end‐stage liver disease (MELD) score had prognostic significance for survival. Both NLR (0.781) and MELD score (0.744) had higher ROC curves, which differed significantly from those for age (0.615) and TBIL (0.691), but not from each other (P = 0.94). NLR ≤2.36 predicted lower mortality (with 91.6% sensitivity and 86.0% negative predictive value), and NLR >6.12 was a warning sign for higher mortality risk (with 90.1% specificity and 80.3% positive predictive value). These results demonstrated that pretreatment NLR was associated with the prognosis of patients with ACHBLF, and elevated NLR predicted poor outcome within 8 weeks. We suggest that NLR cut‐offs of ≤2.36 and >6.12 are powerful markers for predicting mortality in ACHBLF.